Polar Bear (Ursus maritimus) Denning in the Area of the Simpson Peninsula, Nunavut - Van de Velde, OMI, Franz; Stirling, Ian; Richardson, Evan (ARCTIC, 2003)
The locations of polar bear snow dens in winter on the Simpson Peninsula, Nunavut, and nearby islands to the northwest, and information on the sex and age class of a subsample of the occupants of 73 dens, were recorded from interviews with Inuit hunters at Pelly Bay, at intervals from 1937 to 1965 and 1968 to 1969. Hunting bears at winter dens, after locating them with the assistance of dogs, was legal during that period and was widely practiced throughout the Canadian Arctic. For embryos found in utero, mean litter size was 2.0, and two of the eight litters recorded from pregnant females contained three foetuses. Births appeared to occur from about December through early January. For cubs in dens, the mean litter size was 1.88. No litters of three cubs were recorded in winter dens or nearby after departure of the family back to the sea ice in spring. Females accompanied by yearling or two-year-old cubs, subadults, and adult males were also recorded in winter dens during periods of cold weather. The locations of a total of 191 snow dens, occupied during winter, were reported by hunters and marked on maps from memory. Of 180 dens for which the sex of the occupant was recorded, 148 contained females (alone or with an unspecified number of cubs) and 32 had lone males. En se basant sur des entrevues menées à intervalles entre 1937 et 1965, et 1968 à 1969, avec des chasseurs inuits de Pelly Bay, on a consigné les emplacements hivernaux des tanières d'ours polaires dans la péninsule Simpson, au Nunavut, et dans les îles avoisinantes au nord-ouest, ainsi que l'information sur le sexe et le groupe d'âge d'un sous-échantillon des occupants de 73 tanières. Durant cette période, il était permis de chasser l'ours dans sa tanière hivernale, à l'aide de chiens pour la localiser, et cette activité se pratiquait à grande échelle dans tout l'Arctique canadien. Pour les embryons trouvés in utero, la taille moyenne de la portée était de 2,0, et deux des huit portées signalées provenant de femelles gravides contenaient trois ...